Evidence in Civil Law - Czech Republic - Valdhans, Jiří (Institute for Local Self-Government and Public Procurement Maribor, 2017)
The aim of this monograph is to describe and analyse the Czech regulation of evidence taking in its complexity and entirety. Since the monograph is primarily destined for foreign lawyers, not only the legal regulation but also its reflection by the Czech legal theory as well as judicial practice is examined. Thus, the added value of this publication is that it not only describes the legal regulation itself, but also demonstrates on numerous case law produced by Constitutional Court and Supreme Court its real functioning in daily judicial practice. This allows better understanding of how the whole system of evidence taking in the Czech civil procedure works. The publication offers an extensive summary and analysis of regulation of the Czech civil procedure related to the evidence taking. In order to ensure such complex approach, the first part of the monograph is dedicated to fundamental and general principles of the Czech civil procedure which are crucial for the regulation of various aspects of evidence taking. Since the concept of evidence may be different in various jurisdictions, the monograph also examines the value and importance of evidence in the Czech law as well as principles and standards of its collection and subsequent judicial evaluation. Due to the existing differences in various jurisdictions, special attention is dedicated especially to the written evidence and to the role and importance of experts and witnesses in judicial proceedings. The recent judicial practice often has to deal with foreign elements (foreign witness, document in foreign language etc.) in judicial proceedings. For this reason the publication also examines various aspects of translation and interpretation in Czech judicial proceedings. The attention is dedicated also to costs of proceedings. Covered are the principles on which the payment of costs is based as well as rules governing which party and to which extent will bear them. Last chapter examines the concept of "illegally obtained evidence" and "illegal evidence" in the Czech civil procedure. Thus, the focus is put on rules regulating which evidence is according to the Czech Civil Procedure Code as interpreted by Czech highest courts permissible in civil procedure.